City of God - Miramax Films ([s.l.] Miramax, 2004)
In order to tell the story of the place the film tells us the stories of many characters. But all is seen through the eyes of the narrator, Buscape, a poor black kid too frail and scared to become an outlaw but also too smart to be content with an underpaid job. He grows up in a very violent environment. The old are all against him. But he discovers he can see the reality with a different eye : the eye of an artist . Eventually he becomes a professional photographer. That is his redemption.
Screepwriter, Braulio Mantovani ; produced by Andrea Barata Ribeiro, Mauricio Andrade Ramos; directed by Fernando Meirelles.
Alexander Rodrigues, Leandro Firmino Da Hora, Jonathan Haagensen, Phelipe Haagensen.
DVD
In English
Keywords: Feature films